2019
DOI: 10.1177/0192513x19868831
|View full text |Cite
|
Sign up to set email alerts
|

Does Relation Between Women’s Justification of Wife Beating and Intimate Partner Violence Differ in Context of Husband’s Controlling Attitudes in Nigeria?

Abstract: Controlling and domineering attitudes of husbands are risk factors for women’s experience of physical, sexual, and emotional violence in Nigeria. Other studies imply that husband’s attitudes may also influence the risk of women’s justification of wife beating. Consistently, it was hypothesized that husband’s controlling and domineering attitudes would influence the relationship between women’s justification of wife beating and the three types of violence experience. Participants were 19,360 nationally represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 52 publications
(74 reference statements)
3
22
0
Order By: Relevance
“…The differences in findings can be attributed to differences in contextual factors. Nonetheless, there is evidence to show that women in sub-Saharan Africa are more likely to support wife-beating [ 33 ]. For example, a study of seven sub-Saharan Africa countries revealed that about eight in ten women accepted wife-beating [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences in findings can be attributed to differences in contextual factors. Nonetheless, there is evidence to show that women in sub-Saharan Africa are more likely to support wife-beating [ 33 ]. For example, a study of seven sub-Saharan Africa countries revealed that about eight in ten women accepted wife-beating [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This implies that poverty, low education and younger age are risk factors of justified wife-beating. There is substantial evidence to show that these risk factors expose women to actual physical abuse [ 12 , 33 , 39 ]. In this regard, IPV prevention programmes or interventions should focus on more vulnerable populations, such as adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Acceptance of wife abuse (AWA) is a critical factor of the intimate partner violence extensively prevalent in many South Asian countries [ 1 4 ]. Studies conducted in African and Middle-eastern countries such as Ethiopia, Israel, and Nigeria also demonstrated that people’s attitudinal justification of wife abuse is a significant feature of the intimate partner violence against women [ 1 , 5 8 ]. AWA is also a widely talked about topic in the discussion on the primary prevention of violence against women worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Using a similar type of DHS instrument, previous studies also measured the attitudes toward wife beating in other countries like Armenia, Egypt, Ethiopia, India, Nepal, Nigeria, Pakistan, Palestine, etc. [e.g., 1 , 3 , 5 , 8 , 27 , 28 ]. These studies were mostly confined to the acceptance of wife beating.…”
Section: Introductionmentioning
confidence: 99%
“…Both scholars and practitioners advocate for community-based interventions for enhancing refusal of wife abuse among the citizens [ 2 4 ]. Previous studies show that people’s attitude related to wife abuse is a significant feature of IPV perpetrated against women [ 5 9 ]. This is because, in patriarchal societies, people believe that a husband has a right to ‘punish’ his wife under some conditions, e.g., if a wife argues with her husband [ 10 – 12 ].…”
Section: Introductionmentioning
confidence: 99%